2021
DOI: 10.3390/antiox10111731
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Green Tea Supplementation on Antioxidant Status in Adults: A Systematic Review and Meta-Analysis of Randomized Clinical Trials

Abstract: It is well-established that green tea supplementation has antioxidant properties. However, whether green tea supplementation leads to oxidative stress reduction remains unclear, as clinical investigations on this subject have yielded inconsistent outcomes. Consequently, we aimed to determine the effects of green tea supplementation on oxidative stress in adults. A systematic search of English language publications up to 21 August 2021 was carried out in PubMed, Scopus, Embase, and ISI Web of Science, utilizing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 67 publications
0
9
1
Order By: Relevance
“…In the subgroup analysis, a greater increase in TAC was revealed in studies conducted on men, but only a study among women showed a significant reduction in MDA. Our recent meta-analysis on the antioxidant effects of supplementing with all types of green tea demonstrated beneficial effects on TAC in adults; however, in contrast to our results, no reduction in MDA was observed except for low-dose supplementation and individuals with obesity (31) . Although it is becoming increasingly evident that GTE supplementation has a potential role in enhancing TAC (70,71,128) , its effects on MDA as a lipid peroxidation indicator have yet to be established.…”
Section: Effects Of Green Tea Extract Supplementation On Antioxidantscontrasting
confidence: 99%
See 2 more Smart Citations
“…In the subgroup analysis, a greater increase in TAC was revealed in studies conducted on men, but only a study among women showed a significant reduction in MDA. Our recent meta-analysis on the antioxidant effects of supplementing with all types of green tea demonstrated beneficial effects on TAC in adults; however, in contrast to our results, no reduction in MDA was observed except for low-dose supplementation and individuals with obesity (31) . Although it is becoming increasingly evident that GTE supplementation has a potential role in enhancing TAC (70,71,128) , its effects on MDA as a lipid peroxidation indicator have yet to be established.…”
Section: Effects Of Green Tea Extract Supplementation On Antioxidantscontrasting
confidence: 99%
“…Prior meta-analytic works by Rasaei et al (31) and Lin et al (106) reported the effects of GTE supplementation on antioxidant status and obesity, respectively. The present findings exhibit discrepancies with the results of these two recently published meta-analyses, which provided new knowledge on several relevant topics.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is because cancer cells have redox regulation genes, suggesting that low ROS levels are required for their survival; however, the therapeutic approach may be crucial to treating this pathology. Nevertheless, in clinical trials has been shown that antioxidant consumption might be beneficial [ 167 , 168 , 169 , 170 , 171 , 172 ] or have no effect [ 167 , 172 , 173 , 174 ], as it is suggested to depend on the metabolic demand of the individual.…”
Section: Inflammation In Cancermentioning
confidence: 99%
“…It also contains the tea-specific amino-acid ʟ-theanine and caffeine. Meta-analyses of controlled trial data show that the consumption of green tea extracts is associated with a number of cardiovascular and anthropomorphic benefits, including enhanced total antioxidant status [ 162 ], improved glucoregulation [ 163 ] and significant benefits to weight, BMI and waist circumference, irrespective of caffeine content [ 164 ]. Whilst the exercise performance effects of green tea extracts remain unclear, consumption of caffeinated green tea extracts for more than 1 week has been shown to reduce exercise-induced oxidative stress [ 165 ].…”
Section: Multi-component Caffeinated Productsmentioning
confidence: 99%